Acute Promyelocytic Leukaemia With PML – RAR α Fusion Presenting as Pancytopenia and Atypical Morphology – A Case Report: Acute promyelocytic leukemia with peculiar presentation. - Krishna, Sai Sridevi; Hussain, Nazia; Subbiah Rajasekaran, Jayakarthiga (Scripta Medica, 2024)
Acute myeloid leukaemia (AML) is characterised by uncontrolled proliferation of malignant marrow stem cells and is associated with infection, anaemia and bleeding. An improved understanding of pathophysiology has led to revamping the diagnostic, prognostic and therapeutic landscape of AML. AML is classified based on the defined genetic abnormalities and based on the differentiation. AML with predominance of abnormal promyelocytes shows characteristic t(15;17)(q24.1;q21.2) leading to promyelocytic leukaemia – retinoic acid receptor alpha (PML – RARA) fusion oncoprotein. A 75-year-old male with features of acute promyelocytic leukaemia – hypogranular variant with atypical morphology and PML-RARA fusion is presented. The bilobed buttock shaped nuclei is an atypical presentation and is important to diagnose this morphology.